Beyond compliance in the construction sector: Mapping the modern slavery statements through content analysis. Issue 3 (1st November 2022) - Suprun, E; AlMeshari, R; Liu, T; Stewart, R A; Duran, S
Abstract: Modern slavery is considered a widely recognized issue within labour-intensive markets of the construction industry. The recent introduction of the Modern Slavery Act 2018 (Cth) in Australia, has pragmatically pressured construction companies into publishing modern slavery statements that explore the methods in how they have managed to tackle and address the presence of modern slavery within their business and supply chains. This paper, as a part of an ongoing research project, conducts a content analysis to examine Australian modern slavery statements to identify common practices among Australian construction firms. For this purpose, we collected 62 modern slavery statements from construction companies that had issued such statements after the introduction of the regulatory requirement in Australia. The analysis uncovers diverse reporting practices in relation to the corporate commitment and governance, traceability and risk assessment, recruitment, purchasing practices, worker voice, remediation, and monitoring. The paper provides a baseline of understanding about the content and substance of modern slavery statements as a foundation for future research into developing an integrated framework for evaluating the performance on addressing modern slavery.